On the polynomial approximation of a conformal mapping of a domain with nonzero corner - Zherebko, T. M. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Let $G$ be a bounded domain with a Jordan boundary that is smooth at all points except a single point atwhich it forms a nonzero angle. We prove Korevaar’s conjecture on the order of polynomial approximationof a conformal mapping of this domain into a disk. We also obtain a pointwise estimate for the error ofapproximation.